Problematik Kepastian Hukum Darurat Kesehatan Masyarakat Pada Masa Pandemi COVID-19 - Widodo, Hananto; Disantara, Fradhana Putra (Universitas Negeri Surabaya, 2021)
This research is normative research. The purpose of this research is to examine the emergency constitutional law related to the concept of health emergencies as referred to in Law No. 6 of 2018 concerning Health Quarantine; and provide comprehensive analysis and formulation related to future emergency law arrangements. The research method used in this research is a statute approach and a conceptual approach; by using primary and secondary legal materials. The results of this study are the legal implications related to the determination of the health emergency status based on Presidential Decree No. 11 of 2020 has created legal uncertainty, because the government has actually issued Government Regulation No. 21 of 2020 first; is not a Government Regulation on procedures for determining and revoking the status of determining health emergencies. On the other hand, the determination of public health emergencies is not synergistic with its implementation. Furthermore, an ideal arrangement is needed in the future related to public health emergencies in order to achieve legal certainty in public health emergencies. For this reason, a harmonization of the state of danger law is needed or the establishment of a danger state law such as the omnibus bill